A bismuth cluster / CTF composite photocatalyst and its preparation method and application
By growing bismuth clusters in the CTF framework, a bismuth cluster/CTF composite photocatalyst was prepared, which solved the problem of low yield of lignin cracking aromatic monomers, and achieved high-efficiency photocatalytic cracking, improved yield and environmental protection of the process .
Patent Information
- Application Number
- CN202411650961.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-19
AI Technical Summary
In the prior art, during the cracking process of lignin, the maximum yield of aromatic monomers can only reach 27%, and traditional production processes have problems of environmental pollution and dangerous processes.
Using bismuth cluster/CTF composite photocatalyst, the bismuth cluster is grown in the CTF framework by hydrothermal method to achieve fine-tune the electronic structure of the photocatalyst and improve the photocatalytic performance.
The efficient cracking of lignin model compounds is achieved under visible light, with a conversion rate of up to 78.5%, the yield of aromatic monomers is significantly improved, and the process is green, clean and safe.
Smart Images

Figure CN119140154B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalytic degradation, and specifically relates to a bismuth cluster / CTF (triazine framework material) composite photocatalyst and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Oxygenated compounds such as phenols, alcohols, acids, ethers and aldehydes are important source materials in modern chemical industry. Traditionally, oxygenated compounds need to be extracted from petrochemical resources, which not only emits carbon dioxide during the production process, but also involves multiple hazardous processes.
[0004] Lignin is a three-dimensional network polymer formed by random polymerization of syringylpropane units (S type), guaiacylpropane units (G type) and p-hydroxyphenylpropane units (H type). The derivatives of these three aromatic units are connected by CC bonds and CO bonds such as β-O-4, α-O-4, β-1, β-5 and 5-5. The key to the high-value utilization of lignin is how to selectively break the connecting bonds to obtain monophenolic compounds corresponding to the three structural units. The CO bond in the connecting bond has attracted much attention due to its low bond energy and high content. However, according to the inventor's research, the complex connection structure of lignin results in the highest yield of aromatic monomers obtained by breaking the CO bond to only reach 27%. Summary of the invention
[0005] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a bismuth cluster / CTF composite photocatalyst and its preparation method and application. The present invention can not only realize the photocatalytic cracking of lignin by compounding bismuth clusters with CTF, but also realize the efficient separation of photogenerated electrons and holes of the photocatalyst, fine-tune the electronic structure, and improve the efficiency of the photocatalytic process. The production of lignin can improve the yield of aromatic monomers prepared by cracking lignin.
[0006] Specifically, the technical solution of the present invention is as follows:
[0007] In a first aspect of the present invention, a bismuth cluster / CTF composite photocatalyst is provided, wherein the composite photocatalyst comprises a triazine porous framework material CTF and a bismuth cluster confined in the triazine porous framework material CTF; the crystal size of the bismuth cluster is 2-3 nm;
[0008] The preparation method of the bismuth cluster / CTF composite photocatalyst specifically comprises: mixing the triazine porous framework material CTF and the bismuth cluster precursor to carry out a hydrothermal reaction to obtain the bismuth cluster / CTF composite photocatalyst.
[0009] Preferably, the mass ratio of the CTF to the bismuth cluster precursor is 20:1 to 10:1.
[0010] Preferably, the preparation process of the triazine framework material CTF is according to the reference (ZA Lan, M. Wu, ZP Fang, et al. Ionothermal synthesis of covalent triazine frameworks in a eutectic salt for the hydrogen evolution reaction. Angew. Chem. Int. Ed , 2022, 61, 202201482).
[0011] Preferably, the temperature of the hydrothermal reaction is 170-320° C., preferably 170-220° C., and more preferably 180-210° C.; the reaction time of the hydrothermal reaction is 5-15 h.
[0012] Preferably, the bismuth cluster precursor is selected from One or more of; Further preferably, the bismuth cluster precursor is .
[0013] Preferably, the mixture after the hydrothermal reaction is centrifuged, washed and dried at one time; further preferably, the centrifugal speed is 900-1200 rpm, and the centrifugal time is 8-12 min; the drying temperature is 55-65°C, and the drying time is 8-15 h.
[0014] The second aspect of the present invention provides an application of the bismuth cluster / CTF composite photocatalyst described in the first aspect in photocatalytic degradation of lignin.
[0015] The third aspect of the present invention provides a method for preparing aromatic monomers by photocatalytic degradation of lignin, wherein the bismuth cluster / CTF composite photocatalyst described in the first aspect is added to a solution containing lignin and subjected to light treatment.
[0016] Preferably, the added concentration of the bismuth cluster / CTF composite photocatalyst is 2.0-3.0 g / L.
[0017] Preferably, the solution containing lignin contains a lignin model compound; further preferably, the lignin model compound is 2-phenoxy-1-phenylethanol (pp-ol).
[0018] Preferably, the illumination treatment time is 5 to 7 hours, and the optical power density of the visible light is 15 to 20 .
[0019] In order to further improve the yield of preparing aromatic monomers by cracking lignin, the present invention further studies the cracking direction of the CC bond of lignin. Photocatalysis can realize the cracking of CC bonds in a low-energy state with the help of photogenerated electrons and active free radicals, thereby avoiding the re-condensation of aldehydes and phenolic substances and improving the yield of aromatic monomers.
[0020] For C α -C β Bond cleavage, photocatalytic cleavage C α -C β The holes generated from the photocatalyst activate C β -H bond, forming C β Free radical intermediate, then C β The free radical intermediates react with O2 and the H produced by proton reduction. The reaction generates a metastable peroxy intermediate, which finally undergoes electron rearrangement, thereby breaking C α -C β bond. Oxygen and H are required in the reaction pathway The free radicals participate in the reaction, and the presence of oxygen will affect the electrons and H The free radicals are consumed, which greatly limits the reaction efficiency. α -C β In the bond, there are also certain requirements for the oxidation ability of the photocatalyst. OH can indiscriminately attack the connecting bonds in lignin due to its super strong oxidizing ability, which is not conducive to C β The formation of free radical intermediates. Therefore, h + and O2 - Due to the appropriate oxidation capacity, in C β Free radicals and peroxy intermediates play an important role in the formation process. Therefore, in order to enable the photocatalyst to photolyze C α -C β bond, the photocatalyst must have a suitable electronic structure to produce h + and O2 - ; At the same time, the conduction band position of the photocatalyst must be lower than 0.33 V, and the valence band position must be lower than 1.99 V. In order to achieve the purpose of controllable production of free radicals, it is necessary to select a suitable base photocatalyst and fine-tune the electronic structure of the base photocatalyst.
[0021] The combination of bismuth clusters and CTF can greatly enhance the overflow of photogenerated electrons through plasma resonance (LSPR) and inhibit the recombination of photogenerated electrons and holes. At the same time, the bismuth clusters can change their electronic structure due to external stress changes, satisfying the cracking of C α -C β The present invention embeds bismuth clusters into the CTF framework, which can not only improve the stability of bismuth clusters, but also introduce metal sites into CTF to improve catalytic activity. In addition, bismuth clusters and CTF can form a heterojunction, which will accelerate the separation of photogenerated electrons and holes.
[0022] The present invention utilizes a hydrothermal method to confine the growth of bismuth clusters within a CTF framework, and achieves controllable regulation of the electronic structure of the composite material by adjusting the amount of bismuth cluster precursor added, thereby facilitating the improvement of the yield of preparing aromatic monomers by photocatalytic degradation of lignin.
[0023] One or more embodiments of the present invention have at least the following beneficial effects:
[0024] (1) The present invention uses CTF and bismuth to form a composite, utilizes the inherent pores in CTF, confines the growth of bismuth clusters, introduces metal active sites into CTF, and utilizes the LSPR effect to prevent the separation of photogenerated electrons and holes, thereby effectively improving the photocatalytic performance.
[0025] (2) The present invention adopts a hydrothermal method to prepare a bismuth cluster / CTF composite photocatalyst in one step, which not only improves the loading efficiency of bismuth clusters in CTF, but also can fine-tune the electronic structure of the photocatalyst by adjusting the amount of bismuth cluster precursor added to achieve photolysis of C α -C β In addition, the hydrothermal method used in the present invention has the advantages of simple preparation method, short preparation cycle, low equipment requirements, etc.
[0026] (3) Experiments have shown that the bismuth cluster / CTF composite photocatalyst prepared by the present invention can achieve the cracking of lignin model compounds under visible light or natural light, with a cracking conversion rate of up to 78.5%, a yield of benzoic acid of up to 65.2%, benzaldehyde of 81.4%, and a yield of phenyl formate of up to 52.6%, which is green, clean and safe. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0028] Figure 1a This is the electron microscope scanning image of CTF;
[0029] Figure 1bThis is a scanning electron microscope image of CTF stripped by nitric acid;
[0030] Figure 1c This is the electron microscope scanning image after the combination of CTF and bismuth cluster;
[0031] Figure 2a This is a low-magnification transmission electron microscopy image of CB-0;
[0032] Figure 2b This is a high-magnification projection electron microscope image of CB-0;
[0033] Figure 2c This is a low-magnification transmission electron microscopy image of CB-3;
[0034] Figure 2d This is a high-magnification transmission electron microscopy image of CB-3;
[0035] Figure 3a This is the EDS transmission spectrum of the composite photocatalytic material CB-3 prepared in Example 3 of the present invention;
[0036] Figure 3b This is the EDS distribution spectrum of carbon element in the composite photocatalytic material CB-3;
[0037] Figure 3c This is the EDS distribution spectrum of nitrogen in the composite photocatalytic material CB-3;
[0038] Figure 3d This is the EDS distribution spectrum of bismuth element in the composite photocatalytic material CB-3;
[0039] Figure 3e This is the EDS distribution spectrum of oxygen element in the composite photocatalytic material CB-3;
[0040] Figure 4 XRD spectra of the composite photocatalytic materials prepared by the present invention for CTF, Examples 1 to 5 and Comparative Example 1;
[0041] Figure 5 The infrared spectra of the composite photocatalytic materials prepared by the present invention for CTF, Examples 1 to 5 and Comparative Example 1;
[0042] Figure 6 This is an X-ray photoelectron spectrum of the composite photocatalytic material prepared in Example 3 of the present invention;
[0043] Figure 7 The UV-DRS spectra of the composite photocatalytic materials prepared by the present invention for CTF, Examples 1 to 5 and Comparative Example 1;
[0044] Figure 8 The MS curves of the composite photocatalytic materials prepared by the present invention for CTF, Examples 1 to 5 and Comparative Example 1;
[0045] Fig. 9 The electronic structure diagram of the composite photocatalytic material prepared by the present invention for CTF, Examples 1 to 5 and Comparative Example 1;
[0046] Fig.10 The graph is a photocatalytic cracking curve of the composite photocatalytic material prepared by the present invention on CTF, Examples 1-5 and Comparative Examples 1-2 on the lignin model compound. DETAILED DESCRIPTION
[0047] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0048] In view of the low yield of aromatic monomers prepared by existing lignin cracking, the present invention proposes a bismuth cluster / CTF composite photocatalyst and a preparation method and application thereof.
[0049] A first typical embodiment of the present invention provides a bismuth cluster / CTF composite photocatalyst, wherein the composite photocatalyst comprises a triazine porous framework material CTF and a bismuth cluster confined in the triazine porous framework material CTF; the crystal size of the bismuth cluster is 2-3 nm;
[0050] The preparation method of the bismuth cluster / CTF composite photocatalyst specifically comprises: mixing the triazine porous framework material CTF and the bismuth cluster precursor to carry out a hydrothermal reaction to obtain the bismuth cluster / CTF composite photocatalyst.
[0051] In one or more examples of this implementation, the mass ratio of the CTF to the bismuth cluster precursor is 20:1 to 10:1.
[0052] In one or more embodiments of this implementation mode, a hydrothermal method is used to simultaneously compound and synthesize CTF and a bismuth cluster precursor to form a complex of bismuth clusters and CTF; in the hydrothermal method, the prepared CTF is added with bismuth nitrate to react in a hydrothermal reactor, and high temperature and high pressure are used to confine the growth of bismuth clusters in the CTF framework.
[0053] In one or more examples of this implementation mode, the mass ratio of the CTF to the bismuth cluster precursor is 20:1 to 10:1; under this ratio condition, the combination of the prepared bismuth cluster and CTF is optimal.
[0054] In one or more examples of this embodiment, the preparation process of the triazine framework material CTF is according to the reference (ZA Lan, M. Wu, ZP Fang, et al. Ionothermal synthesis of covalenttriazine frameworks in a eutectic salt for the hydrogenevolution reaction. Angew. Chem. Int. Ed , 2022, 61, 202201482).
[0055] In one or more examples of this embodiment, the temperature of the hydrothermal reaction is 170~320°C, preferably 170~220°C, and more preferably 180~210°C; studies have shown that the yield of aromatic monomers increases successively under this temperature condition; the reaction time of the hydrothermal reaction is 5~15 h.
[0056] In one or more examples of this embodiment, the bismuth cluster precursor is selected from One or more of .
[0057] In one or more examples of this embodiment, it is further preferred that the bismuth cluster precursor is .
[0058] In one or more examples of this embodiment, the mixture after the hydrothermal reaction is centrifuged, washed and dried at one time.
[0059] In one or more examples of this implementation mode, the centrifugal speed is 900-1200 rpm, and the centrifugal time is 8-12 min; the drying temperature is 55-65° C., and the drying time is 8-15 h.
[0060] A second typical embodiment of the present invention provides a use of the above-mentioned bismuth cluster / CTF composite photocatalyst in photocatalytic degradation of lignin.
[0061] A third typical embodiment of the present invention provides a method for preparing aromatic monomers by photocatalytic degradation of lignin, wherein the bismuth cluster / CTF composite photocatalyst is added to a solution containing lignin and subjected to light treatment.
[0062] In one or more examples of this implementation, the added concentration of the bismuth cluster / CTF composite photocatalyst is 2.0-3.0 g / L.
[0063] In one or more examples of this embodiment, the solution containing lignin contains a lignin model compound. Specifically, the lignin model compound is 2-phenoxy-1-phenylethanol (pp-ol).
[0064] In one or more embodiments of this implementation mode, the illumination treatment time is 5 to 7 hours, and the optical power density of the visible light is 15 to 20 .
[0065] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0066] The preparation process of CTF in the following examples is based on the reference (ZA Lan, M. Wu, ZP Fang, et al. Ionothermal synthesis of covalent triazine frameworks in a eutectic salt for the hydrogen evolution reaction. Angew. Chem. Int. Ed , 2022, 61, 202201482).
[0067] Example 1 :This embodiment provides a bismuth cluster / CTF composite photocatalyst and a preparation method thereof, which specifically includes the following steps:
[0068] (1) Preparation of covalent triazine framework CTF: 1.0 g of terephthalonitrile was added to 1.0 g of sodium chloride-potassium chloride-zinc chloride eutectic salt and ground for 5 minutes, then quickly placed in a tube furnace and calcined at 200°C for 24 hours. During the calcination process, argon gas was passed at a flow rate of 200 mL / min. The solid obtained after calcination was washed with water three times and then soaked in 1 mol / L hydrochloric acid for 24 hours. The centrifuged solid was washed with methanol, dichloromethane, acetone and tetrahydrofuran, respectively, and finally dried in vacuum at 60°C. The obtained solid was CTFs.
[0069] (2) Preparation of bismuth cluster / CTF composite photocatalyst: 0.5 g of CTF and 0.025 g of Add to 50 mL of deionized water, then sonicate for 30 min. Transfer the resulting mixed solution to a hydrothermal reactor and react at 200 °C for 10 h. After natural cooling, the resulting solution was centrifuged at 1000 rpm for 10 min. After separation, the resulting solid was washed three times with ethanol and water respectively. The resulting product was dried at 60 °C in vacuum for 12 h. The obtained bismuth cluster / CTF composite photocatalyst was recorded as CB-1.
[0070] Example 2 :This embodiment provides a bismuth cluster / CTF composite photocatalyst and a preparation method thereof, which specifically includes the following steps:
[0071] (1) Preparation of covalent triazine framework CTF: 1.0 g of terephthalonitrile was added to 1.0 g of sodium chloride-potassium chloride-zinc chloride eutectic salt and ground for 5 minutes, then quickly placed in a tube furnace and calcined at 200°C for 24 hours. During the calcination process, argon gas was passed at a flow rate of 200 mL / min. The solid obtained after calcination was washed with water three times and then soaked in 1 mol / L hydrochloric acid for 24 hours. The centrifuged solid was washed with methanol, dichloromethane, acetone and tetrahydrofuran, respectively, and finally dried in vacuum at 60°C. The obtained solid was CTFs.
[0072] (2) Preparation of bismuth cluster / CTF composite photocatalyst: 0.5 g of CTF and 0.050 g of Add to 50 mL of deionized water, then sonicate for 30 min. Transfer the resulting mixed solution to a hydrothermal reactor and react at 200 °C for 10 h. After natural cooling, the resulting solution was centrifuged at 1000 rpm for 10 min. After separation, the resulting solid was washed three times with ethanol and water respectively. The resulting product was dried at 60 °C in vacuum for 12 h. The obtained bismuth cluster / CTF composite photocatalyst was recorded as CB-2.
[0073] Example 3 :This embodiment provides a bismuth cluster / CTF composite photocatalyst and a preparation method thereof, which specifically includes the following steps:
[0074] (1) Preparation of covalent triazine framework CTF: 1.0 g of terephthalonitrile was added to 1.0 g of sodium chloride-potassium chloride-zinc chloride eutectic salt and ground for 5 minutes, then quickly placed in a tube furnace and calcined at 200°C for 24 hours. During the calcination process, argon gas was passed at a flow rate of 200 mL / min. The solid obtained after calcination was washed with water three times and then soaked in 1 mol / L hydrochloric acid for 24 hours. The centrifuged solid was washed with methanol, dichloromethane, acetone and tetrahydrofuran, respectively, and finally dried in vacuum at 60°C. The obtained solid was CTFs.
[0075] (2) Preparation of bismuth cluster / CTF composite photocatalyst: 0.5 g of CTF and 0.075 g of Add to 50 mL of deionized water, then sonicate for 30 min. Transfer the resulting mixed solution to a hydrothermal reactor and react at 200 °C for 10 h. After natural cooling, the resulting solution was centrifuged at 1000 rpm for 10 min. After separation, the resulting solid was washed three times with ethanol and water respectively. The resulting product was dried at 60 °C in vacuum for 12 h. The obtained bismuth cluster / CTF composite photocatalyst was recorded as CB-3.
[0076] Example 4 :This embodiment provides a bismuth cluster / CTF composite photocatalyst and a preparation method thereof, which specifically includes the following steps:
[0077] (1) Preparation of covalent triazine framework CTF: 1.0 g of terephthalonitrile was added to 1.0 g of sodium chloride-potassium chloride-zinc chloride eutectic salt and ground for 5 minutes, then quickly placed in a tube furnace and calcined at 200°C for 24 hours. During the calcination process, argon gas was passed at a flow rate of 200 mL / min. The solid obtained after calcination was washed with water three times and then soaked in 1 mol / L hydrochloric acid for 24 hours. The centrifuged solid was washed with methanol, dichloromethane, acetone and tetrahydrofuran, respectively, and finally dried in vacuum at 60°C. The obtained solid was CTFs.
[0078] (2) Preparation of bismuth cluster / CTF composite photocatalyst: 0.5 g of CTF and 0.1 g of Add to 50 mL of deionized water, then sonicate for 30 min. Transfer the resulting mixed solution to a hydrothermal reactor and react at 200 °C for 10 h. After natural cooling, the resulting solution was centrifuged at 1000 rpm for 10 min. After separation, the resulting solid was washed three times with ethanol and water respectively. The resulting product was dried at 60 °C in vacuum for 12 h. The obtained bismuth cluster / CTF composite photocatalyst was recorded as CB-4.
[0079] Example 5 :This embodiment provides a bismuth cluster / CTF composite photocatalyst and a preparation method thereof, which specifically includes the following steps:
[0080] (1) Preparation of covalent triazine framework CTF: 1.0 g of terephthalonitrile was added to 1.0 g of sodium chloride-potassium chloride-zinc chloride eutectic salt and ground for 5 minutes, then quickly placed in a tube furnace and calcined at 200°C for 24 hours. During the calcination process, argon gas was passed at a flow rate of 200 mL / min. The solid obtained after calcination was washed with water three times and then soaked in 1 mol / L hydrochloric acid for 24 hours. The centrifuged solid was washed with methanol, dichloromethane, acetone and tetrahydrofuran, respectively, and finally dried in vacuum at 60°C. The obtained solid was CTFs.
[0081] (2) Preparation of bismuth cluster / CTF composite photocatalyst: 0.5 g of CTF and 0.125 g of Add to 50 mL of deionized water, then sonicate for 30 min. Transfer the resulting mixed solution to a hydrothermal reactor and react at 200 °C for 10 h. After natural cooling, the resulting solution was centrifuged at 1000 rpm for 10 min. After separation, the resulting solid was washed three times with ethanol and water respectively. The resulting product was dried at 60 °C in vacuum for 12 h. The obtained bismuth cluster / CTF composite photocatalyst was recorded as CB-5.
[0082] Comparative Example 1 :This comparative example provides a composite photocatalyst for stripping CTF with nitric acid and a preparation method thereof, which specifically comprises the following steps:
[0083] (1) Preparation of covalent triazine framework CTF: 1.0 g of terephthalonitrile was added to 1.0 g of sodium chloride-potassium chloride-zinc chloride eutectic salt and ground for 5 minutes, then quickly placed in a tube furnace and calcined at 200°C for 24 hours. During the calcination process, argon gas was passed at a flow rate of 200 mL / min. The solid obtained after calcination was washed with water three times and then soaked in 1 mol / L hydrochloric acid for 24 hours. The centrifuged solid was washed with methanol, dichloromethane, acetone and tetrahydrofuran, respectively, and finally dried in vacuum at 60°C. The obtained solid was CTFs.
[0084] (2) Preparation of composite photocatalyst stripped of CTF by nitric acid: 1.0 g of CTF was added to 100 mL of deionized water, and then 1 mL of concentrated nitric acid was added dropwise. The mixture was stirred for 30 min and then transferred to a hydrothermal reactor for reaction at 100 °C for 12 h. After cooling, the mixture was filtered and the obtained solid was vacuum dried at 60 °C for 12 h. The obtained powder was then calcined in a muffle furnace at 350 °C for 3 h. The obtained material was recorded as CB-0.
[0085] Comparative Example 2 :This comparative example provides a composite photocatalyst prepared by a molten salt method and a preparation method thereof, which specifically comprises the following steps:
[0086] (1) Preparation of covalent triazine framework CTF: 1.0 g of terephthalonitrile was added to 1.0 g of sodium chloride-potassium chloride-zinc chloride eutectic salt and ground for 5 minutes, then quickly placed in a tube furnace and calcined at 200°C for 24 hours. During the calcination process, argon gas was passed at a flow rate of 200 mL / min. The solid obtained after calcination was washed with water three times and then soaked in 1 mol / L hydrochloric acid for 24 hours. The centrifuged solid was washed with methanol, dichloromethane, acetone and tetrahydrofuran, respectively, and finally dried in vacuum at 60°C. The obtained solid was CTFs.
[0087] (2) Preparation of bismuth cluster / CTF composite photocatalyst by molten salt method: 1.0 g CTF, 0.075 g , 0.101 g of potassium nitrate, 0.0425 g of sodium nitrate and 0.0595 g of potassium bromide were ground and mixed, and heated in a muffle furnace at a calcination temperature of 270°C for 1 h. The obtained powder was washed with ethanol and DMSO three times, and the final product was dried under vacuum at 40°C. The obtained material was recorded as CB-molten salt.
[0088] Example 6 : This example characterizes the structure of the composite photocatalytic materials prepared in Examples 1 to 5 and Comparative Example 1:
[0089] Figure 1a~Figure 1c Shown are scanning electron microscopy (SEM) images of CTF, CB-0, and CB-3. Figure 1a It can be seen from the figure that CTF is a three-dimensional layered stacking structure. After being treated with nitric acid and high temperature, the layered stacking structure of CTF has been peeled off into a two-dimensional structure (such as Figure 1b shown);
[0090] Figure 1c The figure shows that after the Bi clusters are incorporated, the CTF sheets are bent and curled. This may be because the surface tension of the CTF sheets changes after the Bi clusters are inserted into the CTF framework, resulting in bending and curling.
[0091] Figure 2a~Figure 2d Shown are transmission electron microscopy (TEM) images of CB-0 and CB-3. Figure 2a and Figure 2b It can be seen that CB-0 is a two-dimensional layered structure, which is consistent with the SEM result; Figure 2c and Figure 2d The low-power and high-power transmission electron micrographs of CB-3 are shown. It can be seen from the figure that the two-dimensional morphology of CB-3 is more obvious, and black lattice spots of about 2-3 nm appear on the high-power transmission electron microscope, and the interplanar spacing is 0.31 nm, corresponding to the 200 crystal planes of the bismuth cluster.
[0092] Figure 3a The EDS transmission spectrum of CB-3 is shown. Figure 3b~Figure 3e As can be seen, C, N, Bi and O can all be found in the spectrum, indicating that the bismuth clusters have been successfully dispersed on the surface of CTF.
[0093] Figure 4 The XRD spectra of CTF and CB-X (X=0, 1, 2, 3, 4 and 5) are shown. Among them, 7.7°, 14.6° and 26.8° correspond to the (1010), (1120) and (0002) crystal planes of CTF; the peak at 7.7° corresponds to the in-plane reflection, and the peak at 26.8° corresponds to the interlayer reflection, which indicates that CTF is an AB stacking structure; 23.7°, 30.1°, 32.5° and 42.1° correspond to the (001), (200), (202) and (402) crystal planes of bismuth oxycarbonate (PDF No. 41-1488), respectively. Therefore, the characteristic peaks of CB-X (X=0, 1, 2, 3, 4 and 5) have both the characteristic peaks of bismuth oxycarbonate and CTF, which indicates that the combination of bismuth clusters and CTF is successful.
[0094] Figure 5 The infrared spectra of CTF and CB-X (X = 0, 1, 2, 3, 4 and 5) are shown. For CTF, 3356 and 3186 The peak at 3065 corresponds to the stretching vibration peak of NH; The peak at 2234 corresponds to the stretching vibration peak of CH; The peak at 1366-1663 corresponds to the residual oligomers in the synthesis of CTF; The series of peaks correspond to the stretching vibration peaks of CN in the benzene ring and triazine ring; 1019 The peaks at 820 and 550 correspond to the characteristic peaks of CO. The peaks of 533 and 543 correspond to the bending vibration peaks of CH and NH in the triazine ring. A series of new peaks appearing at , may correspond to Bi-C bonds. In summary, the infrared characteristic peaks of CB-X (X = 0, 1, 2, 3, 4 and 5) cover the characteristic peaks of CTF and Bi clusters, indicating that the combination of CTF and Bi clusters is successful.
[0095] Figure 6 The figure shows the X-ray photoelectron spectrum (XPS total spectrum) of CB-3. It can be seen from the figure that CB-3 contains all the elements of CTF (C and N) and Bi clusters (Bi, O and C), indicating that the combination of CTF and Bi clusters is successful.
[0096] Figure 7Shown are the UV diffuse reflectance absorption spectra (UV-drs) of CTF and CB-X (X = 0, 1, 2, 3, 4 and 5). According to the Kubelka-Munk equation, the energy band gaps of CTF and CB-X (X = 0, 1, 2, 3, 4 and 5) are 3.12, 1.75, 2.49, 2.53, 2.75, 2.69 and 2.61 eV, respectively.
[0097] Figure 8 The MS curves of CTF and CB-X (X = 0, 1, 2, 3, 4 and 5) are shown. According to the MS curves, the flat band potentials of CTF and CB-X (X = 0, 1, 2, 3, 4 and 5) can be calculated to be 0.81, 1.70, 1.79, 1.41, 0.99, 1.75 and 1.54 V (Vvs NHE). According to the band gap and MS curves, the electronic structures of 0.81, 1.70, 1.79, 1.41, 0.99, 1.75 and 1.54 V can be calculated. Fig. 9 as shown).
[0098] from Fig. 9 It can be seen that the electronic structure of the composite material is affected by the amount of bismuth cluster precursor added, and different electronic structures will produce different free radicals. Therefore, by adjusting the amount of addition, the output of free radicals can be controlled.
[0099] Test Example 1 : This test example conducted a photocatalytic cracking experiment of lignin model compound (pp-ol) on the composite photocatalysts prepared by CTF, Examples 1-5 and Comparative Examples 1-2:
[0100] Experimental process: Prepare a pp-ol solution with an initial concentration of 100 mg / L, add the composite photocatalyst obtained in the embodiment and comparative example and the CTF composite material into the pp-ol solution at an addition amount of 2.5 g / L, adsorb to saturation (4 h) under dark reaction conditions, and use visible light (optical power density: 17 ) irradiation, sampling was performed after 6 h of illumination, and the conversion rate of pp-ol and the yield of the product were detected and analyzed.
[0101] The results are as follows Fig.10 As shown, it can be seen that the main products of photocatalytic cracking are phenyl formate, benzaldehyde and benzoic acid. For CTF, the total yields of benzaldehyde, benzoic acid and phenyl formate are 155.4%, while the total yield of the three products of CB-3 is 199.2%, an increase of 28.19%. Among them, the conversion rate of pp-ol of CB-3 is 78.5%, and the conversion rates of benzoic acid, benzaldehyde and phenyl formate are 65.2%, 81.4% and 52.6%, respectively. The calculation formula of yield is as follows:
[0102] Conversion rate (%) = ×100%
[0103] Yield (%) = ×100%
[0104] In contrast, the highest conversion rate of bismuth cluster / CTF composite photocatalyst prepared by molten salt method for pyrolysis of pp-ol in comparative example 2 was only 5.5%, and the conversion rates of benzoic acid, benzaldehyde and phenyl formate were 6.2%, 8.4% and 2.6%, respectively, which were much lower than the conversion rate and yield of bismuth cluster / CTF composite photocatalyst pyrolysis of pp-ol prepared by hydrothermal method.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A bismuth cluster / CTF composite photocatalyst, characterized in that: The composite photocatalyst comprises a triazine porous framework material CTF and a bismuth cluster confined in the triazine porous framework material CTF; the crystal size of the bismuth cluster is 2-3 nm; The preparation method of the bismuth cluster / CTF composite photocatalyst specifically comprises: mixing the triazine porous framework material CTF and the bismuth cluster precursor for hydrothermal reaction to obtain; The mass ratio of the CTF to the bismuth cluster precursor is 20:1-10:
1.
2. The bismuth cluster / CTF composite photocatalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 170-320° C.; the time of the hydrothermal reaction is 5-15 h.
3. The bismuth cluster / CTF composite photocatalyst according to claim 1, characterized in that: The bismuth cluster precursor is selected from One or more of .
4. The bismuth cluster / CTF composite photocatalyst according to claim 1, characterized in that: The mixture after the hydrothermal reaction is centrifuged, washed and dried at one time; wherein the centrifugal speed is 900-1200 rpm, and the centrifugal time is 8-12 min; the drying temperature is 55-65° C., and the drying time is 8-15 h.
5. Use of the bismuth cluster / CTF composite photocatalyst according to any one of claims 1 to 4 in photocatalytic degradation of lignin.
6. A method for preparing aromatic monomers by photocatalytic degradation of lignin, characterized in that: The bismuth cluster / CTF composite photocatalyst according to any one of claims 1 to 4 is added to a solution containing lignin and subjected to light treatment.
7. The method for preparing aromatic monomers by photocatalytic degradation of lignin as claimed in claim 6, characterized in that: The addition concentration of the bismuth cluster / CTF composite photocatalyst is 2.0-3.0 g / L.
8. The method for preparing aromatic monomers by photocatalytic degradation of lignin as claimed in claim 6, characterized in that: The solution containing lignin contains a lignin model compound; the lignin model compound is 2-phenoxy-1-phenylethanol.
9. The method for preparing aromatic monomers by photocatalytic degradation of lignin as claimed in claim 6, characterized in that: The illumination treatment time is 5-7 h, and the light power density of visible light is 15-20 .
Citation Information
Patent Citations
Metal Bi nano-particle loaded Ni-MOF composite material as well as preparation method and application thereof
CN117364156A